P098 Aryl hydrocarbon receptor ameliorates intestinal barrier dysfunction in colitis by regulating the myosin light-chain kinase signalling pathway. (16th January 2018) - Ma, H; Zhang, H
Abstract: Background: Accumulating evidence suggests that the aryl hydrocarbon receptor (AhR) plays an important role in regulating the function of the intestinal barrier, especially the immune response, in patients with inflammatory bowel disease and in mouse models. However, whether AhR aids to protect the intestinal mucosal mechanical barrier remains unknown. In this study, we hypothesised that AhR ameliorates intestinal mucosal mechanical barrier in colitis. Methods: Experimental colitis was induced in male C57BL/6 wild-type mice and AhR knockout (AhR KO) mice using 2, 4, 6-trinitrobenzenesulfonic acid (TNBS). Correspondingly, the AhR agonist 6-formylindolo [3, 2-b] carbazole (FICZ) and the AhR antagonist CH223191 were used to treat Caco-2 monolayers in the presence of tumour necrosis factor α (TNF-α). Colonic mucosal barrier permeability and myosin light-chain kinase (MLCK) signalling pathway were investigated both in vivo and vitro. Results: In vivo experiments, it was found that TNBS-induced colitis was more severe in AhR KO mice than in C57BL/6 wild-type mice. The intestinal permeability was significantly higher in AhR KO mice than in wild-type mice induced by TNBS. The expression and fluorescence of tight junction protein in AhR KO mice were lower than that in wild-type mice induced by TNBS. The increased expression of MLCK and phosphorylated MLC (pMLC) indicated that this pathway was open. In cell culture experiments, treatment with FICZ caused retention of the tight junction protein, alleviated the increase of intestinal permeability, and mitigated epithelial injury. However, treatment with CH223191 facilitated the unblocking of the MLCK-pMLC signalling pathway and repressed the protein expression of tight junction in vitro. Conclusions: AhR plays an important role in ameliorating epithelial barrier dysfunction in colitis through regulating the MLCK signalling pathway, suggesting that AhR may be a suitable entrance of addressing this condition.